Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1172/jci108284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 3-day fast and of ethanol on splanchnic metabolism of FFA, amino acids, and carbohydrates in healthy young men.

Abstract: A B S T R A C T Splanchnic metabolism was studied to quantify changes underlying the fatty liver, hyperlipemia, and hypoglycemia produced by ethanol. Four subjects fasted for 15 h were compared with five subjects fasted for 69 h under basal conditions and during continuous intravenous infusion of sufficient ethanol to give a concentration of 3-5 mM in arterial blood plasma. Splanchnic storage of fatty acids was estimated from the difference between uptake of FFA and secretion of derived products. Basal values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Palmitate comprised an average of 24.2% of the total circulating FFA, a figure that also compares well with reported values (32,34,38). The overall mean palmitate ,umol/kg per min, both values similar to those found in prior investigations (36,37,(39)(40)(41). As noted by others (39,(41)(42)(43)(44), the net inflow transport of fatty acids was directly proportional to the plasma concentration (Fig.…”
Section: Methodssupporting
confidence: 88%
“…Palmitate comprised an average of 24.2% of the total circulating FFA, a figure that also compares well with reported values (32,34,38). The overall mean palmitate ,umol/kg per min, both values similar to those found in prior investigations (36,37,(39)(40)(41). As noted by others (39,(41)(42)(43)(44), the net inflow transport of fatty acids was directly proportional to the plasma concentration (Fig.…”
Section: Methodssupporting
confidence: 88%
“…The shift in the redox state supports a possible mechanism for the inhibition of hepatic gluconeogenesis (HGN) and corroborates the occurrence of alcohol-induced hypoglycemia, especially in malnourished individuals where renal and hepatic glycogen stores are compromised. While not a consistent observation, reports in fasted humans [5][6][7] and fasted rats [8][9][10] have demonstrated a significant decline in blood glucose concentration after a substantial ingestion of ethanol.…”
Section: Consumption On Glucose Homeostasismentioning
confidence: 96%
“…This work confirmed that plasma FFA are the predominant source of VLDL-TGFA in postabsorptive humans. By comparing normal with diabetic dogs, 39 normotriglyceridemic subjects with those with primary hypertriglyceridemia 40 and alterations produced by glucose-6-phosphatase deficiency (von Gierke disease) 41 and infusion of ethanol, 42 it became evident that increased secretion of VLDL-triglycerides derived from FFA could account some hypertriglyceridemic states (short-term insulin deficiency, glucose-6-phosphatase deficiency), but not others (long-term insulin deficiency, primary endogenous hypertriglyceridemia). 1 By simultaneously measuring splanchnic fatty oxidation (to CO 2 and ketone bodies), we could estimate splanchnic (presumably hepatic) storage of fatty acids as well.…”
Section: Research At the National Heart Institute (1953 To 1956)mentioning
confidence: 99%
“…45 For example, the reduction in hepatic oxidation of FFA by ethanol in subjects fasted for 3 days led to accumulation of triglycerides in the liver at a rate that could readily account for the rapid development of fatty liver in poorly nourished alcoholics. 42 The status of the liver in glucose-6-phosphatase deficiency indicated a "fed" phenotype (in which oxidation of glycogen replaced that of FFA) with large increases in VLDL-triglyceride production. By contrast, peripheral tissues were confronted with hypoglycemia owing to reduced hepatic glucose production.…”
Section: Research At the National Heart Institute (1953 To 1956)mentioning
confidence: 99%